The Effect of Red Ginger Decoction And Honey On Blood Pressure Among The Elderly With Hypertension - Janno Sinaga; Henny Syapitri; Novita Aryani; Yuyun Kristela Berutu (Window of Health : Jurnal Kesehatan, 2026)
Hypertension remains a major public health problem among older adults. In 2025, according to data from the WHO, 1.28 billion people aged 30–79 years will experience an increased risk of cardiovascular morbidity and mortality. Complementary herbal therapy has been increasingly used as a non-pharmacological approach to blood pressure control. To determine the effect of red ginger (Zingiber officinale var. rubrum) and honey decoction combination therapy on blood pressure reduction among elderly patients with hypertension at Tinada Primary Health Center. This study employed a quasi-experimental one-group pretest–posttest design. A total of 32 elderly individuals with hypertension grade 1–2 participated as the sample, selected using purposive sampling from 105 registered hypertensives. Respondents received 250 ml of red ginger decoction (100 g boiled in 500 ml water until 250 ml remained) mixed with 15 ml pure honey once daily for 7 consecutive days. Blood pressure was measured before and after intervention using a calibrated digital sphygmomanometer. Data were analyzed using a paired t-test with a significance level of p<0.05. The mean systolic blood pressure decreased from 180.90 ± 12.51 mmHg to 160.10 ± 12.82 mmHg, while the mean diastolic pressure decreased from 94.50 ± 7.75 mmHg to 86.30 ± 5.56 mmHg. Statistical analysis showed a significant reduction in systolic and diastolic blood pressure (p = 0.000). The combination of red ginger decoction and honey is related to a decline in blood pressure among elderly hypertensive patients and may serve as a complementary therapy in hypertension management.